Community Empowerment through Sustainable Development Goal (SDGS) Village Program - Luthfiyah, Siti Nur Azizatul; Rizki, Via Lailatur (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2024)
Focusing on poverty alleviation, Presidential Regulation No. 166/2014 underscores the importance of a comprehensive strategy, strong coordination, and sustained efforts as the country's top priority. The strategy is aimed at reducing poverty and ensuring that the basic rights of citizens are fulfilled through inclusive, equitable and sustainable development. The goal is to create a better and fairer life for everyone, in line with the SDGs' Village Community goals as well as the SDGs' global goals that place community empowerment as a key method in tackling poverty. This research was conducted using a qualitative approach and is descriptive in nature. Data collection in this study was carried out through three main approaches: making observations, conducting in-depth interviews, and reviewing related documents. Data were analyzed using descriptive qualitative analysis using the Miles and Huberman interactive model, which includes data condensation, data display and drawing and verification of results. triangulation of techniques, triangulation of sources, and member checks ensured the validity of the data. The results showed that the villagers formed their own SDGs by volunteering.